PENERAPAN STRATEGI PEMBELAJARAN KOMUNIKATIF UNTUK MENIGKATKAN KEMAMPUAN MENULIS LAPORAN SISWA KELAS VA SDN PAJAGALAN II - Ali Harsojo (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
This research uses classroom action research methods to improve the learning conditions of students in class V SDN Pajagalan II Academic Year 2017. The subjects of this research is class VA class consisting of 40 students. The research instrument used was direct observation techniques and the use of learning achievement tests. Data were analyzed using qualitative analysis. According to the results of data analysis known that an increase in student achievement from the first cycle to the second cycle. In the first cycle the number of children who completed the study were 65% and on this cycle increases by about 25% to the value of completeness achieved was 90%. The average value of grade achieved in the previous cycle is 72.5 rose to 78.4, up 5.9 points. And the percentage of classical completeness has shown satisfactory results, namely 90%.